The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1471-4159.2004.02700.x
|View full text |Cite
|
Sign up to set email alerts
|

The arachidonic acid 5‐lipoxygenase inhibitor nordihydroguaiaretic acid inhibits tumor necrosis factor α activation of microglia and extends survival of G93A‐SOD1 transgenic mice

Abstract: Familial forms of amyotrophic lateral sclerosis (ALS) can be caused by mutations in copper, zinc-superoxide dismutase (SOD1). Mice expressing SOD1 mutants demonstrate a robust neuroinflammatory reaction characterized, in part, by up-regulation of tumor necrosis factor alpha (TNFa) and its primary receptor TNF-RI. In an effort to identify small molecule inhibitors of neuroinflammation useful in treatment of ALS, a microglial culture system was established to identify TNFa antagonists. Walker EOC-20 microglia ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 62 publications
(160 reference statements)
4
85
0
2
Order By: Relevance
“…These results show that ROS may perform essential functions for both the induction of airway inflammation and for the pathogenesis of asthmatic diseases. Previous studies have revealed that NDGA exerts pleiotropic effects capable of influencing a wide variety of cellular processes, including TGF-β-induced signal transduction, leukocyte chemotaxis, myoblast cell differentiation, cancer cell proliferation, and viral proliferation in infected cells (Goetzl et al, 1980;Gnabre et al, 1995;Lee et al, 2003;West et al, 2004;Ito et al, 2005;Youngren et al, 2005;Arasaki et al, 2007). However, its anti-inflammatory effects in allergic inflammation have been investigated to a lesser degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that ROS may perform essential functions for both the induction of airway inflammation and for the pathogenesis of asthmatic diseases. Previous studies have revealed that NDGA exerts pleiotropic effects capable of influencing a wide variety of cellular processes, including TGF-β-induced signal transduction, leukocyte chemotaxis, myoblast cell differentiation, cancer cell proliferation, and viral proliferation in infected cells (Goetzl et al, 1980;Gnabre et al, 1995;Lee et al, 2003;West et al, 2004;Ito et al, 2005;Youngren et al, 2005;Arasaki et al, 2007). However, its anti-inflammatory effects in allergic inflammation have been investigated to a lesser degree.…”
Section: Discussionmentioning
confidence: 99%
“…To that end, we utilized Nordihydroguaiaretic acid (NDGA), LOXs inhibitor. The results of previous studies have shown that NDGA exerts pleiotropic effects capable of influencing a broad variety of cellular processes, including growth factor-and TNF-induced signal transduction, leukocyte chemotaxis, myoblast cell differentiation, cancer cell proliferation, and viral proliferation in infected cells (Goetzl et al, 1980;Gnabre et al, 1995;Lee et al, 2003;West et al, 2004;Ito et al, 2005;Youngren et al, 2005;Arasaki et al, 2007). It can also induce the expression of NOS, regulate calcium channel activity, and inhibit the growth of β-amyloid protofibrils (Ramasamy et al, 1999;Huang et al, 2004;Moss et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nordihydroguaiaretic acid (NDGA) is a drug that affects a wide variety of cellular processes, including growth factorand tumor necrosis factor-induced signal transduction (Domin et al, 1994;Lee et al, 2003;West et al, 2004), leukocyte chemotaxis (Goetzl, 1980), myoblast cell differentiation (Ito et al, 2005), cancer cell proliferation (Avis et al, 1996;McDonald et al, 2001;Seufferlein et al, 2002;Youngren et al, 2005), and viral proliferation in infected cells (Gnabre et al, 1995). It can also induce nitric-oxide synthase expression (Ramasamy et al, 1999), regulate calcium channel activity (Korn and Horn, 1990;Huang et al, 2004), and inhibit growth of ␤-amyloid (1-40) protofibril (Moss et al, 2004).…”
mentioning
confidence: 99%
“…mice on an NDGA-diet from presymptomatic stage to end-point have a 32% increase in median lifespan as well as a reduced motoneuron loss and astrocytosis [197].…”
Section: G93amentioning
confidence: 99%